STACKED LONG SHORT-TERM MEMORY AND HIDDEN MARKOV MODEL FOR SPEECH EMOTION RECOGNITION-A SYSTEMATIC REVIEW - Joshua, Bature Hassan; Temitayo, Matthew Fagbola; Lawrence, Bunmi Adewole; Daniel, Dauda Wisdom (FUDMA Journal of Sciences, 2026)
Speech Emotion Recognition (SER) plays a vital role in various real-world applications, from mental health diagnostics to human-computer interaction. This research examines the integration of Stacked Long Short-Term Memory (LSTM) networks and Hidden Markov Models (HMM) for SER, addressing the limitations of traditional models like Gaussian Mixture Models (GMM) and Support Vector Machines (SVM). While GMMs and SVMs offer decent performance, their inability to model temporal dynamics limits their accuracy in detecting complex emotions. The proposed hybrid model leverages LSTM’s strength in handling sequential data and HMM’s ability to model emotional transitions, making it highly suitable for real-world noisy environments. Preprocessing techniques such as MFCC and LPCC are applied to enhance feature extraction, and benchmark datasets like IEMOCAP and RAVDESS are used for evaluation. Finally, The Systematic review highlights the superior role of the hybrid model's performance on SER and sets the stage for a significant shift in future research in addressing bias and fairness in SER systems by combining LSTM and HMM as hybrid model.  In recent studies, context-aware emotion recognition models are commonly evaluated using existing datasets such as IEMOCAP, MELD, DailyDialog, and SEMAINE, which provide conversational and multimodal emotional data. Features used often include acoustic features as MFCCs, spectrograms, prosodic features, linguistic features as BERT or transformer embeddings, and visual cues such as facial landmarks or video frames. Many models also incorporate contextual embeddings from transformers, graph attention networks, or sequential memory modules to capture speaker history and emotional shifts.
Keywords: SER; LSTM; HMM; GMM; Hybrid model